(untitled) (Journal of Fiber Bioengineering and Informatics, 2016)
In order to improve some defects of pure chitosan membrane, such as the high brittleness and poor flexibility etc.. This paper adopted a simple and effective method to realize the performance optimization by blending with Poly Lactic Acid (PLA) and Poly (Vinyl Alcohol) (PVA). The result indicated that compared with pure CS membrane, moisture absorption rate and Water Vapor Transmission Rate (WVTR) of CS ⁄ PLAand CS ⁄ PVAblend membranes have been greatly improved. With a certain amount of the PLA or PVA, the breaking elongation of the blend membrane rise steadily. The physical properties of CS ⁄ PLA blend membrane are better than the CS ⁄ PVA's, so the research for CS ⁄ PLA blend membrane is expanded. With the Scanning Electron Microscopy (SEM) images, it observed that the CS ⁄ PLA blend membrane's porosity is improved after freeze-drying, and have better porous structure, the pore size and morphology with different blending ratios changed significantly. Besidethe SEM images, CS ⁄ PLA blend membranes' Fourier transform infrared spectroscopy (FTIR) reveal that the strong hydrogen bonds formed between CS and PLA, which is consistent with the conclusions of the Differential Scanning Calorimetry (DSC). The DSC curve analysis shows that the decomposition temperatures of the blend membrane decrease firstly and then increase with the decrease of CS content. The comprehensive property of the porous membranes is optimal point where the CS content is 60%. The good properties, such as moisture regain, porosity, and water vapor transmission rate, of the kind of CS ⁄ PLA or CS ⁄ PVA blend membranes suggested a potential application in wound dressing.